Halofuginone for cancer treatment: A systematic review of efficacy and molecular mechanisms. (November 2022) - Mi, Li; Zhang, Yujie; Su, Anping; Tang, Minghai; Xing, Zhichao; He, Ting; Wu, Wenshuang; Li, Zhihui
Graphical abstract: Highlights: We provide a comprehensive review of the most recent anticancer studies reported for Halofuginone (HF). HF exhibits significant anticancer activity and synergistic effects in chemotherapy/radiotherapy/virus for the treatment of various cancers in vitro and in vivo. HF could induce cell cycle arrest, apoptosis and autophagy, inhibit cell proliferation, invasion, migration and angiogenesis, and disturb the tumor microenvironment in tumor cells. The anticancer effect of HF might be associated with the induction of the amino acid starvation response by HF in response to the inhibition of glutamyl-prolyl-tRNA synthetase. Abstract: Cancer is still considered a "hopeless case", which seriously endangers human health. Therefore, it is of great significance to research and develop novel anticancer drugs. Active natural products play an important role in anticancer drug discovery by providing lead compounds. Halofuginone (HF), as a derivative of febrifugine, an alkaloid originally isolated from the plant Dichroa febrifuga, is used for the prevention and treatment of coccidiosis and malaria in poultry. In recent years, HF has shown excellent anticancer activity and great clinical potential for treating various cancers. Despite enormous progress, a thorough elaboration of the proposed mechanism and mode of action is absent. Herein, we provide a comprehensive review of the most recent anticancer studies reported for HF and a rationale for further exploring the potential application of HF in overcoming cancer in the future.